(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Enriching natural materials is essential for developing eco-friendly composites in structural and automotive applications. The aim of this work is toÂ extensively characterize new natural cellulosic fiber extracted from Sesbania rostrata stem.Â Â Â Â Â Â S. rostrata fibers (SRFs) show cellulose content of 64.36 % with a range of tensile strength from 156 to 460 MPa and have a low density of 1.365 g/cm3. SRFs has crystallinity index of 58.41%, which is comparable with that of other common natural fibers. Furthermore, SRFs can resist the degradation of cellulose up to 246Â°C, which is revealed by thermogravimetric analysis.Â